The effect of intravenous high-dose glucocorticoids and orbital decompression surgery on sight-threatening thyroid-associated ophthalmopathy - Wen, Yun (International journal of ophthalmology, 2019)
To report the effects of intravenous high-dose glucocorticoids (ivGC) and orbital decompression (OD) surgery for treatment of sight-threatening thyroid-associated ophthalmopathy (TAO).AIMTo report the effects of intravenous high-dose glucocorticoids (ivGC) and orbital decompression (OD) surgery for treatment of sight-threatening thyroid-associated ophthalmopathy (TAO).A retrospective review of medical records from patients with sight-threatening TAO [definite or highly suspected dysthyroid optic neuropathy (DON)] treated with ivGC (60 cases) and OD (25 cases) was conducted at the Zhongshan Ophthalmic Center between January 2001 and January 2009. Patients were initially treated with ivGC (ivGC group). If no significant improvement in visual function was obtained, they then received OD surgery (OD group). The pre- versus post-treatment efficacies of either ivGC or OD in these patients were assessed using several indices, including visual acuity, intraocular pressure, ocular alignment, ocular motility, and exophthalmos.METHODSA retrospective review of medical records from patients with sight-threatening TAO [definite or highly suspected dysthyroid optic neuropathy (DON)] treated with ivGC (60 cases) and OD (25 cases) was conducted at the Zhongshan Ophthalmic Center between January 2001 and January 2009. Patients were initially treated with ivGC (ivGC group). If no significant improvement in visual function was obtained, they then received OD surgery (OD group). The pre- versus post-treatment efficacies of either ivGC or OD in these patients were assessed using several indices, including visual acuity, intraocular pressure, ocular alignment, ocular motility, and exophthalmos.Nighty-one eyes had definite DON while 79 were considered to have highly suspected DON. In the ivGC group, 51 individuals (85.0%) eventually demonstrated normal vision, while 10 patients (16.7%) demonstrated a reduction in deviation (P<0.01), and 35 cases (58.3%) showed slight improvements in ocular motility (P<0.01). In OD group, visual acuity improved in 24 cases (96.0%, P<0.01) and all patients showed varying reductions of exophthalmos (mean: 4.35±1.13 mm, P<0.01). Eight cases (32.0%) experienced an 8-15 PD reduction of deviation and ocular motility improved in 12 cases (48.0%), while 3 patients (12.0%) developed new-onset strabismus with diplopia post-surgically (P<0.01). Patients were followed up at an average of 1.55±1.07y.RESULTSNighty-one eyes had definite DON while 79 were considered to have highly suspected DON. In the ivGC group, 51 individuals (85.0%) eventually demonstrated normal vision, while 10 patients (16.7%) demonstrated a reduction in deviation (P<0.01), and 35 cases (58.3%) showed slight improvements in ocular motility (P<0.01). In OD group, visual acuity improved in 24 cases (96.0%, P<0.01) and all patients showed varying reductions of exophthalmos (mean: 4.35±1.13 mm, P<0.01). Eight cases (32.0%) experienced an 8-15 PD reduction of deviation and ocular motility improved in 12 cases (48.0%), while 3 patients (12.0%) developed new-onset strabismus with diplopia post-surgically (P<0.01). Patients were followed up at an average of 1.55±1.07y.Both ivGC and OD show good therapeutic efficacy in the treatment of sight-threatening TAO. The presence of extremely poor eyesight (≥0.5logMAR) was corrected in some patients with ivGC alone, thus sparing these patients from subsequent OD surgery. In patients who were refractory to steroids, subsequent OD surgery often provided satisfactory outcomes, however, new-onset strabismus with diplopia was observed in 12.0% of these cases.CONCLUSIONBoth ivGC and OD show good therapeutic efficacy in the treatment of sight-threatening TAO. The presence of extremely poor eyesight (≥0.5logMAR) was corrected in some patients with ivGC alone, thus sparing these patients from subsequent OD surgery. In patients who were refractory to steroids, subsequent OD surgery often provided satisfactory outcomes, however, new-onset strabismus with diplopia was observed in 12.0% of these cases.